Acute Renal Failure, Microangiopathic Haemolytic Anemia, and Secondary Oxalosis in a Young Female Patient. (19th July 2011) - Stepien, Karolina M.; Prinsloo, Peter; Hitch, Tony; McCulloch, Thomas A.; Sims, Rebecca
Abstract : A 29-year old female presented with a one-week history of vomiting, diarrhoea, abdominal pain, and headache. On admission, she had acute renal failure requiring dialysis. Tests revealed a hemolytic anemia with thrombocytopenia. An initial diagnosis of thrombotic thrombocytopenic microangiopathy was made and plasma exchange was instigated. However, renal biopsy did not show thrombotic microangiopathy but instead revealed acute kidney injury with mild tubulointerstitial nephritis and numerous oxalate crystals, predominantly in the distal tubules. The patient had been taking large doses (>1100 mg daily) of vitamin C for many months. She also gave a history of sclerotherapy using injections of an ethylene glycol derivative for superficial leg veins. The patient completed five sessions of plasma exchange and was able to discontinue dialysis. She eventually achieved full renal recovery. She has now discontinued sclerotherapy and vitamin supplementation.